Design of a Multiband Hexagonal Patch Antenna for Wireless Communication Systems. Issue 3 (4th May 2022) - Fadamiro, Akinwale O.; Ntawangaheza, Jean D.; Famoriji, Oluwole J.; Zhang, Zhongxiang; Lin, Fujiang
Abstract : A multiband hexagonal patch antenna with a compact size of 35 × 30 mm is proposed in this paper using FR4 substrate. The proposed patch antenna consists of four rectangular slots and a circular slot etched into the patch with a coaxial feeding network matched to 50ohms input impedance. The proposed antenna's performance shows a good multiband operating at 2.40, 5.03 and 8.67 GHz with their return losses at −28, −17, and −22 dB, respectively. The comparison between the measurement and simulation results validates the proposed design, satisfying the requirements for wireless communication applications.